Alterations of the X Chromosome in Lymphocytes of Alzheimer’s Disease Patients - Spremo-Potparevic, Biljana; Bajic, Vladan; Perry, George; Zivkovic, Lada (Current Alzheimer Research, 2015)
Chromosomal alterations as a sign of genetic instability are a feature of Alzheimer’s disease (AD). Assessment of the genetic instability of non-neuronal cells of AD patients may provide a method to diagnose or monitor prognosis of the disease. Considering the importance of X chromosome alterations in the possible etiology of AD females, we used fluorescent in situ hybridization (FISH) for the centromere region of the X chromosome to determine aneuploidy, for a possible correlation with premature centromere division (PCD, X) in lymphocytes of AD females and age-matched controls. In AD patients, our results showed a marked and significant increase in the frequency of the X chromosome aneuploidy comparing with age matched controls (p<0.001). Also, a significant difference was detected in the PCD, X frequency between AD females when compared with age matched controls (p<0.001). In addition, a strong (R2=0.97, n=20) and significant (p<0.001) correlation was found between the frequency of aneuploidy and PCD, X in the AD group. Our results support the view that AD is a generalized systematic disease where PCD is to be considered as a stable sign of disease leading to aneuploidy.
Keywords: Alzheimer’s disease